ANALISIS PENGARUH KUALITAS AUDITOR DAN KOMITE AUDIT TERHADAP COST OF DEBT DENGAN USIA PERUSAHAAN SEBAGAI VARIABEL PEMODERASI (Studi Pada Perusahaan yang Melakukan IPO di BEI Tahun 2008-2012) - Rian Eko Prasetyo; Surya Raharja (Diponegoro Journal of Accounting, 2013)
The aim of this study is to examine the effect of auditor quality and the audit committee in the lowering cost of debt for the company and whether the private age of company at the time of IPO becomes the moderating variable among of auditor quality, audit committees and the cost of debt. This study uses firm private age as a proxy for capital cycle and existing of lending relationship to view the likely extent of debt dependence prior to IPO. Auditor quality and the audit committee is considered as an effective monitoring activity mechanism to increase confidence of the stakeholder of the company. The population of this study is a company doing an IPO on the Indonesia Stock Exchange in 2008-2012. The method of selecting the sample using purposive sampling criteria, total sample obtained are 52 companies. The analysis method of this study is multiple regression analysis with the Moderated Regression Analysis (MRA).The result show that the auditor quality significant negative effect on the cost of debt. Private age of firm as moderating variables may affect the relationship of auditor quality and cost of debt. While the audit committee did not significantly affect the cost of debt and private age of firm as moderating variables can not affect the relationship of the audit committee and the cost of debt.